Late Pleistocene eruptive recurrence in the post-collisional Mt. Hasan stratovolcanic complex (Central Anatolia) revealed by zircon double-dating - Friedrichs, Bjarne; Harvey, Janet C.; Schmitt, Axel Karl (Journal of volcanology and geothermal research, 2020)
Mt. Hasan (3262 m) is the second highest stratovolcano in Central Anatolia, Turkey, and is considered active based on a ca. 9 ka explosive summit eruption that was arguably depicted in a Neolithic mural at the nearby Çatalhöyük archaeological site. Besides evidence for Holocene activity of Mt. Hasan, its eruptive chronostratigraphy and hazard potential remain poorly constrained. Here, we apply (U-Th)/He thermochronology in combination with U-Th-Pb crystallization ages (zircon double-dating), including a novel population-based approach to disequilibrium correction of (U-Th)/He data, in an attempt to determine the eruption ages of strategically sampled lavas and pyroclastic deposits and to refine the Late Pleistocene chronostratigraphy of Mt. Hasan. During the Late Pleistocene, Mt. Hasan erupted multiple interfingering andesitic lava flows along with block-and-ash-flows. Seven of these lava flows, typically the stratigraphically youngest in a particular segment around the two central vents of the volcano, yielded Late Pleistocene eruption ages between 91.9 ± 3.9 and 18.1 ± 2.4 ka (uncertainties stated at 1σ). An even younger block-and-ash-flow was deposited on the western flank of the volcano at 13.5 ± 1.5 ka, which together with a ca. 9 ka small-volume explosive summit eruption define the youngest activity at the main edifice of Mt. Hasan. Collectively, these data indicate a Late Pleistocene recurrence of at least one eruptive phase every ca. 5-15 ka. New volume estimates for the Quaternary edifice of ~130-180 km3 translate into an integrated long-term eruptive magma flux of ~0.3 km3/ka, which is just slightly higher than Late Pleistocene flux estimates based on lava flow geochronology and volumes determined by analysis of digital elevation models. This long-term eruptive flux estimate is similar to those of stratovolcanoes in continental arcs, indicating that eruptive productivity in post-collisional settings can match that of active continental margins. All Mt. Hasan eruptions, including the Holocene event, sampled zircon which crystallized coeval with earlier eruptive phases, indicating longevity of the magma plumbing system. Along with ongoing fumarole activity and evidence for mid-crustal low seismic velocity zones, this suggests that a subvolcanic magma reservoir remains active to the present day.
Gesehen am 10.11.2020